THE METHOD OF BEHAVIOUR DETECTION ON MORAL HAZARD IN FINANCIAL STATEMENT - Fitri Ismiyanti (Journal of Management and Business, 2014)
The purpose of this study is to detect fraud or moral hazard on the financial statements that prepared by the company. This research uses financial ratio analysis to detect financial fraud and moral hazard. Fundamental contribution of this study is on the detection of fraud in the financial statements in accordance with GAAP, so investors and external parties able to find any intentional distortion of financial statements of the company. In addition, the condition of this deviation can also be traced in relation to its influence on the financial performance of the company, and those who benefited from the fraud. In particular the contribution of research is to provide information on the occurrence of fraudulent financial reporting that occurred in several companies in Indonesia. This research provides empirical evidence on the effectiveness of financial ratio analysis to detect fraudulent financial reporting. In addition, the calculation of financial ratios is expected to be early detection of potential fraudulent financial reporting in any form. This study uses financial statement ratio analysis to detect financial fraud. The results showed of 23 financial ratios are used, only two liquidity ratios (current ratio) and profitability (ROE) which can be used to help determine that a company is likely to carry out fraud in the financial statements..